Effects of mud contamination to cement casing bonding - Samsuri, Ariffin; Subbiah, Surej Kumar (1998)
One of the failure in petroleum well cementing operations is due to the effect of mud contamination on cement slurry while displacement process. Mud material, especially mud additives have a great influence towards the cement-casing bonding and the cement compressive strength. Since then, it is necessary to observe the effect of the mud contamination to the cement bonding and strength. Cement slurry which has been contaminated by the mud is then cured for 24 hours within the temperature range of 150-250oF and pressure range of 2000-3000 psi before it is tested for the compressive strength and bonding. From the laboratory experiments, it was found that increasing in the mud rheologies especially yield point will reduced the cement bonding and compressive strength significantly and it is compulsory to control the mud rheologies to ensure the whole cementing operation reaches the optimum stage with the adequate cement strength.